A Router Architecture for Connection-Oriented Service Guarantees in the MANGO Clockless Network-on-Chip - Bjerregaard, Tobias; Sparso, Jens (Design, Automation and Test in Europe, 2005)
On-chip networks for future system-on-chip designs need simple, high performance implementations. In order to promote system-level integrity, guaranteed services (GS) need to be provided. We propose a network-on-chip (NoC) router architecture to support this, and demonstrate with a CMOS standard cell design. Our implementation is based on clockless circuit techniques, and thus inherently supports a modular, GALS-oriented design flow. Our router exploits virtual channels to provide connection-oriented GS, as well as connection-less best-effort (BE) routing. The architecture is highly flexible, in that support for different types of BE routing and GS arbitration can be easily plugged into the router.